PATH46 Familial mutations in the RNA binding gene FUS result in cellular mislocalisation of the protein. Issue 11 (22nd October 2010) - Rogelj, B; Shaw, C E; Vance, C; Hortobagyi, T
Abstract : ALS is a fatal neurodegenerative disorder. We have recently identified mutations in the gene encoding fused in sarcoma (FUS) as a cause of the familial and sporadic ALS. FUS shares functional domains with TDP-43 and the identification of mutations in a second RNA binding protein indicates the importance of RNA metabolism to motor neurones. Post-mortem analysis of three cases with FUS mutations showed FUS -immunoreactive cytoplasmic inclusions and predominantly lower motor neurone degeneration. Furthermore, we demonstrate that FUS mutations disrupt a nuclear localising signal (NLS) and result in the sequestration of wild type protein within cytoplasmic stress granules. In ALS patients carrying FUS mutations, nuclear FUS is significantly reduced in motor neurones containing cytoplasmic inclusions. The cellular phenotype of cytoplasmic FUS accumulation within stress granules is rescued by the addition of a wild-type FUS NLS to the mutant protein. Our findings show some parallels with TDP-43 mislocalisation in frontotemporal dementia (FTD) and ALS and are consistent with the mislocalisation of mutant FUS protein acting in a dominant negative fashion.